Hydroxyurea treatment of children with hemoglobin SC disease1. Issue 2 (4th September 2012) - Yates, Amber M.; Dedeken, Laurence; Smeltzer, Matthew P.; Lebensburger, Jeffrey D.; Wang, Winfred C.; Robitaille, Nancy
Abstract The efficacy of hydroxyurea in hemoglobin SC (HbSC) patients is not well documented. We describe the long‐term response to hydroxyurea in children with clinically severe HbSC. In 15 patients, hydroxyurea resulted in a significant increase in mean corpuscular volume (MCV) and fetal hemoglobin (HbF) and a significant decrease in episodes of acute chest syndrome and hospitalization for pain; there was no effect on hemoglobin level. The most significant side effect was thrombocytopenia, which led to discontinuation of treatment in one patient. This study suggests that hydroxyurea has efficacy and is safe for long‐term therapy in patients with HbSC. Pediatr Blood Cancer 2013;60:323–325. © 2012 Wiley Periodicals, Inc.